Nancy Drew and the crew Case of the sneaky snowman The fashion disaster - Keene, Carolyn; Pamintuan, Macky (Aladdin Paperbacks New York, NY, 2015)
Case of the sneaky snowman: Nancy Drew investigates a missing snowman